2017
DOI: 10.3390/ijms18102072
|View full text |Cite
|
Sign up to set email alerts
|

Splitting the “Unsplittable”: Dissecting Resident and Infiltrating Macrophages in Experimental Autoimmune Encephalomyelitis

Abstract: Macrophages predominate the inflammatory landscape within multiple sclerosis (MS) lesions, not only regarding cellularity but also with respect to the diverse functions this cell fraction provides during disease progression and remission. Researchers have been well aware of the fact that the macrophage pool during central nervous system (CNS) autoimmunity consists of a mixture of myeloid cells. Yet, separating these populations to define their unique contribution to disease pathology has long been challenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…In addition, it was shown that microglia upregulate CD45 expression under different disease conditions ( 8 , 41 ). Furthermore, monocytes downregulate Ly6C and Ccr2 during their differentiation into macrophages after infiltrating brain tissue ( 6 , 8 ), resulting in issues regarding the distinction of microglia and peripheral monocyte/macrophages in disease conditions.…”
Section: Microglia Origin and Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was shown that microglia upregulate CD45 expression under different disease conditions ( 8 , 41 ). Furthermore, monocytes downregulate Ly6C and Ccr2 during their differentiation into macrophages after infiltrating brain tissue ( 6 , 8 ), resulting in issues regarding the distinction of microglia and peripheral monocyte/macrophages in disease conditions.…”
Section: Microglia Origin and Homeostasismentioning
confidence: 99%
“…MS lesions are surrounded by normal appearing white matter, where microglial activation may occur as well ( 99 ). It is very difficult to interpret the distinct roles of microglia and monocyte-derived macrophages in MS pathology, since both macrophage populations are present in MS lesions ( 6 ). This mixed cell population of microglia and monocyte-derived macrophages has been investigated on transcriptomic level in human MS tissue ( 38 , 100 ).…”
Section: Microglial Activation States From a Transcriptome Point Of Vmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of lineage tracing models and markers that allow for discrimination of microglia and recruited myeloid cells and highlights advantages and limitations is provided in Table 1 . For review see also ( 122 ).…”
Section: Molecular Identities Of Microglia and Macrophages In Brain Mmentioning
confidence: 99%
“…Monocyte-derived macrophages are another major cell type of the peripheral immune system that have a major contribution to pathology in MS. One difficulty in studying the impact these cells have, however, is the difficulty in distinguishing infiltrating peripheral macrophages from CNS-resident microglia in and around MS-like lesions. As such, many older studies investigating the contribution of infiltrating macrophages and resident microglia in MS either used controversial approaches to classify cells into one or the other [ 112 ], or simply did not attempt to distinguish the cell types. Recent innovations in both methodology and scientific understanding, however, have allowed for separate classification of these cells with greater precision and accuracy, and it has now been established that infiltrating peripheral macrophages have a specific and important role in resolution of demyelinating lesions in EAE [ 113 ].…”
Section: Peripheral Immune Mirnasmentioning
confidence: 99%